2 2 2 = ( 3 2 2 2 − 1 ) 2
Is it possible to make the equation above true by inserting the appropriate operations? Any operations and functions can be used.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A binary operation on N is any function f : N × N → N . So we can define a function f such that f ( 2 , 2 ) = 3 , f ( 3 , 2 ) = ( 3 2 2 2 − 1 ) 2 and defined in any way we want for any other pair (For example f ( x , y ) = 0 if x = 2 , 3 and y = 2 ), and note it like f ( x , y ) = x ⊗ y .
Then: ( 2 ⊗ 2 ) ⊗ 2 = 3 ⊗ 2 = ( 3 2 2 2 − 1 ) 2 And since any operations and functions can be used, ⊗ can. And there are infinitely many other ways to do it.
So, if you cannot think of an operation that works... create one yourself.
Problem Loading...
Note Loading...
Set Loading...
This is another obvious cheat. d x d ( 2 × 2 × 2 ) = d x d ( 3 2 2 2 − 1 ) 2
A non-cheating is 2 × 2 × 2 = ( 3 2 2 2 − 1 ) 2